Maintenance of unity and territorial integrity of Russia: some constitutional legal problems - S. V. Ivanov (Правоприменение)
The subject. The article is devoted to the analysis of public authorities’ activities in order to strengthen unity of domestic legal space and the people of Russia with regard to constitutional legal support of the state unity and territorial integrity of the Russian Federation.The purpose of the article is to make a critical analysis of implementing a system that consists of constitutional legal rules and procedures of regulatory impact on the unity of domestic legal space and the people of Russia with the aim of increasing the effectiveness of their implementation.The methodological basis of the study includes general-scientific methods (analysis and syn-thesis, system-structural approach) as well as academic methods (formal-legal method, method of interpretation of legal acts).Results, scope. Consistent constitutional legal support of the state unity and territorial integrity of the Russian Federation requires elimination of defects and gaps in legal regulation and improvement of law enforcement practice. In particular, it is necessary to eliminate the practice of denial of a state registration of political parties on insignificant formal grounds in order to implement guarantees of the unity of the people of Russia.Conclusions. The consistent strengthening of the unity of domestic legal space and the people of the Russian Federation is of paramount importance to the constitutional and legal support of its state unity and territorial integrity. It is necessary to eliminate a number of legal defects and to make law enforcement practice more effective in order to implement these constitutional values.